2011
DOI: 10.1590/s0004-282x2011000500010
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between motor and sensory functions in upper limb chronic hemiparetics after stroke

Abstract: Objective: Describe the somatosensory function of the affected upper limb of hemiparetic stroke patients and investigate the correlations between measurements of motor and sensory functions in tasks with and without visual deprivation. Method: We applied the Fugl-Meyer Assessment (FMA), Nottingham Sensory Assessment (NSA), and several motor and sensory tests: Paper manipulation (PM), Motor Sequences (MS), Reaching and grasping (RG) Tests Functional (TF), Tactile Discrimination (TD), Weight Discrimination (WD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 23 publications
5
32
0
11
Order By: Relevance
“…PROG at all three doses led to significant improvement in outcome measures, but again, the P8 group had the best performance overall. A number of studies have reported that somatosensory stimulation results in improved motor functions and motor cortex plasticity in stroke patients (Ward and Cohen 2004; Scalha et al 2011). We found that PROG reduced somatosensory neglect, which in turn led to better motor recovery in the sub-acute post-stroke period.…”
Section: Discussionmentioning
confidence: 99%
“…PROG at all three doses led to significant improvement in outcome measures, but again, the P8 group had the best performance overall. A number of studies have reported that somatosensory stimulation results in improved motor functions and motor cortex plasticity in stroke patients (Ward and Cohen 2004; Scalha et al 2011). We found that PROG reduced somatosensory neglect, which in turn led to better motor recovery in the sub-acute post-stroke period.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, eye movements have been shown in stroke investigations to be a sensitive biomarker for cognitive and motor recovery (149, 150). Additionally, poststroke patients display unique pathophysiologic phenotypes that may include tactile deficits (151153), proprioceptive losses (154, 155), hemiparesis and related motor synergies (156158), and spasticity (159161), which would suggest that these new sensory and motor “states” postinjury create new relationships between receptor and effector, requiring the need for re-integration (162164). …”
Section: Impairment Of the Visuomotor Systemmentioning
confidence: 99%
“…Whereas in MVF, much of the cognitive workload can be offloaded onto the mirror, more mental effort is required in NF-MIT23. Given the fact, that stroke-induced motor impairment seldom comes in isolation, but is typically accompanied by cognitive impairment24, sensibility loss2526 or MI ability impairment27, the question thus is which patients are actually still able to perform MI with their paretic body side2829, and when is a bottom-up motor percept induct more applicable. Whereas in NF-MIT the patient is supported by a neurofeedback signal, which helps to perform the mental act and facilitates imagery-induced motor cortex activation3031, no neurofeedback signal can typically be provided in MVF.…”
mentioning
confidence: 99%